Pengaruh Cognitive Flexibility Terhadap Peningkatan Perilaku Hidup Bersih dan Sehat Pada Siswa Sekolah Dasar - Ratna Ayu Wulandari; Nadiroh Nadiroh; Bagus Sumargo (LPPM Universitas Negeri Jakarta, 2022)
The emergence of various diseases that often attack school-age children (ages 6-14) was generally related to Clean and Healthy Life Behavior. The purpose of clean and healthy life behavior in schools is to empower students, teachers, and the community in the school environment so that they know and are willing and able to practice clean and healthy life behavior and take an active role in realizing healthy schools. Therefore, instilling clean and healthy life behavior values in schools is an essential and absolute need that can be done through persuasive activities and cognitive flexibility abilities. Cognitive flexibility is the ability to think about things in different ways. This study aims to determine the effect of cognitive flexibility on improving clean and healthy life behavior in elementary school students. The method used is a quantitative correlation, with data analysis using SPSS. Data collection was carried out by distributing questionnaires through Google Form. The study was conducted in one elementary school in Jakarta in grades 1st to 6th, with 125 students as respondents. The improvement of Clean and Healthy Life Behavior is assessed from 3 indicators of cognitive flexibility and 8 indicators of clean and healthy life behavior in schools.